Cal State East Bay Student Affairs and Enrollment Management Newsletter - Division of Student Affairs and Enrollment Management:::::: (2025)
A monthly newsletter that began in December 2024 intended "to highlight some of the new and highest priority efforts taking place to recruit and retain students."